2011
DOI: 10.1038/gene.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

Gene–gene interaction among cytokine polymorphisms influence susceptibility to aggressive periodontitis

Abstract: Aggressive periodontitis (AgP) is a multifactorial disease. The distinctive aspect of periodontitis is that this disease must deal with a large number of genes interacting with one another and forming complex networks. Thus, it is reasonable to expect that gene-gene interaction may have a crucial role. Therefore, we carried out a pilot case-control study to identify the association of candidate epistatic interactions between genetic risk factors and susceptibility to AgP, by using both conventional parametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…On the other hand, Gore et al, found that neutrophils from patients with advanced Page 10 of 20 A c c e p t e d M a n u s c r i p t periodontitis and carrying IL-1B (C+3954T) allele 2 produced increased IL-1b levels compared to patients without this allele but the differences were not significant (22). In contrast to other studies, Scapoli et al, conclude no association between AgP and IL1B gene was found in Italian Caucasian population (46), and a study of Galbraith et al, found no significant relationship between the genotype status and the level of cytokine production (47). While Santtila et al, found that allele 2 of the IL-1B polymorphism was associated with decreased IL-1b secretion (48).…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, Gore et al, found that neutrophils from patients with advanced Page 10 of 20 A c c e p t e d M a n u s c r i p t periodontitis and carrying IL-1B (C+3954T) allele 2 produced increased IL-1b levels compared to patients without this allele but the differences were not significant (22). In contrast to other studies, Scapoli et al, conclude no association between AgP and IL1B gene was found in Italian Caucasian population (46), and a study of Galbraith et al, found no significant relationship between the genotype status and the level of cytokine production (47). While Santtila et al, found that allele 2 of the IL-1B polymorphism was associated with decreased IL-1b secretion (48).…”
Section: Discussionmentioning
confidence: 90%
“…Genetic variations of human SEPS1 located on chromosome 15q26.3, which was suggested to contain quantitative trait loci infl uencing infl ammation-related disorders such as type 2 diabetes, Alzheimer's disease, and celiac disease (45)(46)(47), were reported to be strongly associated with infl ammation in Mexican American individuals ( 13 ). Recently, variation in the SEPS1 gene locus has been reported to be associated with coronary heart disease ( 48 ), preeclampsia ( 49 ), gastric cancer ( 50 ), non-small cell lung cancer ( 51 ), and aggressive periodontitis ( 52 ). Some of the single nuclear polymorphisms in the SEPS1 gene were found in the conserved ERSE in the promoter region: this appears to alter inducibility of SEPS1 by ER stress and its Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A case–control study to identify the association of candidate genes epistatic interactions between genetic risk factors and susceptibility to aggressive periodontitis by using parametric analysis and higher order interaction models [20] has shown that: 1) within 14 candidate genes chosen in scientific literatures selenoprotein S (SEPS1) and tumor necrosis factor receptor superfamily member 1B (TNFRSF1B), have a possible role in determining host individual susceptibility to the disease; 2) an association between IL-6 and Fc-γ receptor polymorphism with periodontitis; 3) no the association of IL-1 cluster gene polymorphism with aggressive periodontitis.…”
Section: Introductionmentioning
confidence: 99%